Landscape of the epigenetic regulation in wound healing - Yu, Honghao; Wang, Yichen; Wang, Dawei; Yi, Yi; Liu, Zeming; Wu, Min; Wu, Yiping; Zhang, Qi (Frontiers in Physiology, 2022)
Wound healing after skin injury is a dynamic and highly coordinated process involving a well-orchestrated series of phases, including hemostasis, inflammation, proliferation, and tissue remodeling. Epigenetic regulation refers to genome-wide molecular events, including DNA methylation, histone modification, and non-coding RNA regulation, represented by microRNA (miRNA), long noncoding RNA (lncRNA), and circular RNA (circRNA). Epigenetic regulation is pervasively occurred in the genome and emerges as a new role in gene expression at the post-transcriptional level. Currently, it is well-recognized that epigenetic factors are determinants in regulating gene expression patterns, and may provide evolutionary mechanisms that influence the wound microenvironments and entire healing course. Therefore, this review aims to comprehensively summarize the emerging roles and mechanisms of epigenetic remodeling in wound healing. Moreover, we also pose the challenges and future perspectives related to epigenetic modifications in wound healing, which would bring novel insights to accelerated wound healing.